PRotective vEntilation with veno-venouS lung assisT in respiratory failure: A protocol for a multicentre randomised controlled trial of extracorporeal carbon dioxide removal in patients with acute hypoxaemic respiratory failure. (May 2017) - McNamee, JJ; Gillies, MA; Barrett, NA; Agus, AM; Beale, R; Bentley, A; Bodenham, A; Brett, SJ; Brodie, D; Finney, SJ; Gordon, AJ; Griffiths, M; et al.
One of the few interventions to demonstrate improved outcomes for acute hypoxaemic respiratory failure is reducing tidal volumes when using mechanical ventilation, often termed lung protective ventilation. Veno-venous extracorporeal carbon dioxide removal (vv-ECCO2 R) can facilitate reducing tidal volumes. pRotective vEntilation with veno-venouS lung assisT (REST) is a randomised, allocation concealed, controlled, open, multicentre pragmatic trial to determine the clinical and cost-effectiveness of lower tidal volume mechanical ventilation facilitated by vv-ECCO2 R in patients with acute hypoxaemic respiratory failure. Patients requiring intubation and mechanical ventilation for acute hypoxaemic respiratory failure will be randomly allocated to receive either vv-ECCO2 R and lower tidal volume mechanical ventilation or standard care with stratification by recruitment centre. There is a need for a large randomised controlled trial to establish whether vv-ECCO2 R in acute hypoxaemic respiratory failure can allow the use of a more protective lung ventilation strategy and is associated with improved patient outcomes.